APPLICATIVE CONSTRUCTIONS IN JAVANESE (Universitas Negeri Semarang, 2010)
Applicative constructions refer to those in which an underlying indirect object or oblique is realised as a coreargument. The applied argument replaces P and in most languages becomes the direct object. In mostinstances, the verb usually bears a distinctive inflection expressing the semantic relation borne by the directobject. In Javanese applicative constructions could be intransitive-based and transitive-based, and theyinvolve oblique to 2 advancement or 3-2 advancement. The N- prefix on the verb, the deletion ofpreposition, and the suffix –i/ni or –ake mark the advancement to direct object. The suffix –i/ni is used tomark locative, recipient and destination advancement, whereas the suffix –ake is used to mark benefactiveand instrumental advancement. It is also possible that advancement to direct object is not marked with anysuffix.